High-fat Diet and Physical Exercise Differentially Modulate Adult Neurogenesis in the Mouse Hypothalamus. (21st February 2019) - Klein, C.; Jonas, W.; Wiedmer, P.; Schreyer, S.; Akyüz, L.; Spranger, J.; Hellweg, R.; Steiner, B.
Highlights: High-fat diet (HFD) increased neurogenesis and the fraction of POMC neurons in the adult arcuate nucleus (ArcN). Physical exercise increased cell proliferation in the ArcN of HFD-fed mice. HFD-induced increase in the amount of microglia was reduced to control levels by physical exercise. Physical exercise reduced body weight gain due to HFD. Abstract: The hypothalamus has emerged as a novel neurogenic niche in the adult brain during the past decade. However, little is known about its regulation and the role hypothalamic neurogenesis might play in body weight and appetite control. High-fat diet (HFD) has been demonstrated to induce an inflammatory response and to alter neurogenesis in the hypothalamus and functional outcome measures, e.g. body weight. Such modulation poses similarities to what is known from adult hippocampal neurogenesis, which is highly responsive to lifestyle factors, such as nutrition or physical exercise. With the rising question of a principle of neurogenic stimulation by lifestyle in the adult brain as a physiological regulatory mechanism of central and peripheral functions, exercise is interventionally applied in obesity and metabolic syndrome conditions, promoting weight loss and improving glucose tolerance and insulin sensitivity. To investigate the potential pro-neurogenic cellular processes underlying such beneficial peripheral outcomes, we exposed adult female mice to HFD together with physical exercise and evaluated neurogenesis and inflammatory markers in the arcuate nucleus (ArcN) of the hypothalamus. We found that HFD increased neurogenesis, whereas physical exercise stimulated cell proliferation. HFD also increased the amount of microglia, which was counteracted by physical exercise. Physiologically, exercise increased food and fat intake but reduced HFD-induced body weight gain. These findings support the hypothesis that hypothalamic neurogenesis may represent a counter-regulatory mechanism in response to environmental or physiological insults to maintain energy balance.